The fundamental limits of recycling : from minerals processing to computer aided design of automobiles and other consumer goods - Reuter, Markus Andreas (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Process Engineering)--Stellenbosch University, 2006.